Nitrate reductase activity in different moisture tolerant genotypes of maize (Zea mays L.) in flooding and non-flooding regimes - CHAND, GURDEV; PRAVA, CHANDER (Journal of Soil and Water Conservation, 2022)
Influence of water logging on the nitrate reductase activity in different moisture tolerant varieties of maize (Zea mays L.) in flooding and non-flooding regimes under Varanasi conditions of different cultivars MT-981, MT-982, MT-983, MT-984, VC-2, MT-991 and MT-992 were estimated. Experiment was performed under field conditions. The flooding of the maize varieties is not the factor to increase or decrease the nitrate reductase activity (NRA) in leaves but it is varietal response to the flooding condition is the deciding factor. At the age of 72 days of the plants prolonged days after flooding i.e. 29 days nitrate reductase activity significantly decreases in all the varieties except MT-991, and MT-992 where no significant change. In normal condition i.e. non flooding condition the nitrate reductase activity in leaves of the maize varieties was observed, increases with the age of the plants and it is highest at 89 days age among the age group studied. The flooding condition significantly decreases the NRA in leaves of the maize varieties and this effect is not even annotated with the prolonged period of flooding treatment. This minimizing effect on the flooding nitrate reductase activity in all the varieties begins with flooding is enable to regain the normal activity an increase it again.